Application Biofloqua Technology as a Solution to Increase the Survival of Snakehead Fish (Chana striata) in the Cirebon Region - Amri Suganda Sianturi; Ajeng Mudaningrat (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
The application of biofloc-aquaponics (biofloqua) in snakehead fish (Chana striata) cultivation is the right solution to increase production and meet high market demand in the Cirebon area. The method used in the preparation of this article is a literature study from various national and international reputable journals. The application of biofloc-aquaponics technology (biofloqua) can be done by making circular planting ponds accompanied by ropes and wires attached to the top of the pond to bind the charcoal and water spinach, winds are made in each pond with 5 additional points of molasses and probiotic swamps as starters. Snakehead fish (Chana striata) was stocked and adjusted, then given three times a day commercial feeding and protein diet. The kale seeds were sown on rockwool substrate in a damp room without sunlight and after roots and a few leaves appeared on the rockwool substrate, they were planted in aquaponic containers. The application of technology Biofloc-aquaponics (biofloqua) can improve the life recovery of snakehead fish (Chana striata). The integration of biofloqua technology can be used as a simple cultivation system in producing fish and vegetables.